2017
DOI: 10.1097/sla.0000000000001880
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Value of Colon Surgery in Michigan

Abstract: A colectomy perioperative care bundle in Michigan is associated with improved value of surgical care. We will expand efforts to implement perioperative care bundles in Michigan to improve outcomes and reduce costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…With regard to bundle implementation, an inverse relationship between compliance rates and SSI rates has been previously demonstrated. 18 Our overall compliance rate with the OSI prevention bundle was 62.5%. Compliance rates with individual elements of the bundle ranged from 84.9% to 100%.…”
Section: Discussionmentioning
confidence: 81%
“…With regard to bundle implementation, an inverse relationship between compliance rates and SSI rates has been previously demonstrated. 18 Our overall compliance rate with the OSI prevention bundle was 62.5%. Compliance rates with individual elements of the bundle ranged from 84.9% to 100%.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies showed that a bundle of infection control measures was shown to be extremely successful in reducing catheter-related blood stream infections [2] and ventilatorassociated pneumonia [10]. Jaffe et al reported that SSI rates is 0.9% when there is a compliance to all care bundle components and the SSI rate is 17.9% when bundle adherence was lowest [11]. Moreover, Richards et al stated that the application of evidence-based practices to reduce catheter-associated urinary tract infections decrease the infection ratio from 2.34 to an infection ratio of less than 1.0 [12].…”
Section: Original Research Articlementioning
confidence: 99%
“…23,26,45 Adherence to preoperative bathing with chlorhexidine and/or use of chlorhexidine-impregnated wipes ranged between 89% and 92%. 16,52 Three studies reported SSI incidence by bundle adherence: Jaffe et al 27 observed an overall SSI rate of 0.9% versus 16% when there was adherence to all 6 bundle elements versus only 0-2 bundle elements, respectively. Vu et al 34 reported an overall SSI rate of 4.5% versus 6.5% in the highest versus lowest adherence quartile, respectively (P = .049).…”
Section: Composition Of Colorectal Infection Prevention Bundlesmentioning
confidence: 99%